Pengaruh Promosi Social Media Instagram, Word of Mouth, and Personal Selling terhadap Keputusan Pembelian Produk Kosmetik Toko Kotty Banda Aceh - Misdawati Misdawati; Amelia Amelia; Suryani Murad (Pusat Riset dan Inovasi Nasional, 2026)
cosmetic industry is considered a promising sector as it relates to basic human needs and evolving lifestyle trends, resulting in increasingly intense market competition. In Banda Aceh, Kotty Store offers a variety of local and international cosmetic products; however, fluctuating and declining sales indicate weaknesses in the application of Personal Selling and the influence of external factors such as weather conditions. These issues may cause consumers to experience difficulties in selecting products and potentially switch to competing stores. This study aims to analyze the effect of Instagram promotion, word of mouth, and Personal Selling on consumer purchasing decisions for cosmetic products at Kotty Store in Banda Aceh, both simultaneously and partially. This research employed a quantitative approach with a survey method by distributing questionnaires to 99 respondents. Data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that Instagram promotion, word of mouth, and Personal Selling have a significant effect on purchasing decisions, both partially and simultaneously. These findings highlight the important role of these three marketing strategies in encouraging consumers to make purchasing decisions at Kotty Store.